Oral Administration of L-Citrulline Changes Brain Free Amino Acid and Monoamine Metabolism in Heat-Exposed Broiler Chickens - Chowdhury, Vishwajit S.; Han, Guofeng; Elhussiny, Mohamed Z.; Ouchi, Yoshimitsu; Tran, Phuong V.; Nishimura, Haruka; Haraguchi, Shogo; Cockrem, John F.; Bungo, Takashi; Furuse, Mitsuhiro (Frontiers in Animal Science, 2022)
High ambient temperatures (HT) in summer are becoming more severe due to global warming, leading to severe adverse effects on poultry production. Recently, we have reported that oral administration of L-citrulline (L-Cit) can minimize hyperthermia in chickens under HT. However, whether oral L-Cit can enter the brain, the center for thermoregulation, has not been studied. We investigated the effects of oral administration of L-Cit on free amino acids and monoamines in the diencephalon region of the brain of heat-exposed broilers. Broilers were treated with L-Cit (40 mmol/20 ml/bird), then moved to a chamber at HT (30 ± 1°C) or to a thermoneutral temperature (CT: 22 ± 1°C) chamber for 2 h. Control groups were given methyl cellulose solution and placed in the CT or HT chambers. After 2 h of exposure to HT, there were increased brain concentrations of Cit in comparison with concentrations in broilers exposed to CT, whereas brain ornithine (Orn) concentrations were decreased, and arginine (Arg) concentrations were not changed. Interestingly, oral administration of L-Cit increased brain concentration of Cit, Arg and Orn under both CT and HT. Tryptophan and its metabolite, serotonin (5-HT) concentrations were lower in the brain under HT than under CT. HT did not change brain concentrations of tyrosine, but dopamine (DA, a metabolite of tyrosine) concentrations decreased, and methoxyhydroxyphenylglycol (MHPG, a metabolite of DA) concentrations increased in comparison with CT. Oral administration of L-Cit decreased brain concentrations of both tryptophan and tyrosine under CT and HT without changing 5-HT; however, DA levels declined under HT. Moreover, MHPG concentrations increased. In conclusion, these results suggest that metabolism of amino acids and metabolism of DA can be enhanced in the brain by oral administration of L-Cit. Metabolic changes in the brain in response to oral administration of L-Cit may influence the thermoregulatory center in the brain, leading to a reduction in body temperature and conferring thermotolerance in heat-exposed broiler chickens.